2017
DOI: 10.1155/2017/9130608
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon: A Protein Crucial to the Multiple Functions of Immunomodulatory Drugs as well as Cell Metabolism and Disease Generation

Abstract: It is well known that cereblon is a key protein in autosomal recessive nonsyndromic mental retardation. Studies have reported that it has an intermediary role in helping immunomodulatory drugs perform their immunomodulatory and tumoricidal effects. In addition, cereblon also regulates the expression, assembly, and activities of other special proteins related to cell proliferation and metabolism, resulting in the occurrence and development of metabolic diseases. This review details the multiple functions of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…Moreover, CRBN KO H1299 and CRBN KO MCF7 cells revealed marked increases of autophagy activation in response to LPS stimulation. Although the direct evidence of CRBN being capable of affecting cancer progression is insufficient, many reports have suggested that CRBN is closely related to the proliferation and metabolism of normal and tumor cells (6, 3537). To expand the multifunctional roles of CRBN in cancer progression induced by autophagy, we examined the abilities of cancer cell migration and invasion in CRBN KO H1299 and CRBN KO MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CRBN KO H1299 and CRBN KO MCF7 cells revealed marked increases of autophagy activation in response to LPS stimulation. Although the direct evidence of CRBN being capable of affecting cancer progression is insufficient, many reports have suggested that CRBN is closely related to the proliferation and metabolism of normal and tumor cells (6, 3537). To expand the multifunctional roles of CRBN in cancer progression induced by autophagy, we examined the abilities of cancer cell migration and invasion in CRBN KO H1299 and CRBN KO MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies on CRBN have focused on the multiple effects of immunomodulatory imide drugs (IMiDs) (6, 3739). It has also been suggested that the cellular expression of CRBN influences cell metabolism and leads to disease in the absence of IMiDs, indicating the various functions and cellular mechanisms of CRBN (38).…”
Section: Discussionmentioning
confidence: 99%
“…A recent x-ray structure of POI-PROTAC-E3 ternary complex provides strong evidence to support this mechanism [27]. Although there are > 600 E3 ubiquitin ligases, only several with small molecule ligands have been used for designing PROTACs, including Skp1-Cullin-F box complex containing Hrt1 (SCF) [28], Von Hippel-Lindau tumor suppressor (VHL) [29], Cereblon (CRBN) [30], inhibitor of apoptosis proteins (IAPs) [31], and mouse double minute 2 homolog (MDM2) [32]. Representative ligands of these E3s are showed in Fig.…”
Section: What Is Protac?mentioning
confidence: 99%
“…Considerable efforts have been made to identify new target proteins of CRBN and their roles in the normal and pathophysiology of the cell. Clinically, CRL4 Crbn have been recognized as an important therapeutic target for several diseases, including multiple myeloma, leprosy, and hematopoietic cancer ( 28 - 30 ). CRBN is likely to affect a variety of brain-related functions and diseases; however, the physiological function of CRBN in the brain is still unclear.…”
Section: Discussionmentioning
confidence: 99%